2023
DOI: 10.1007/s43477-023-00077-4
|View full text |Cite
|
Sign up to set email alerts
|

Common Elements Approaches to Implementation Research and Practice: Methods and Integration with Intervention Science

Abstract: We propose that common elements approaches can advance implementation research and practice and facilitate pragmatic use of intervention and implementation evidence. Common elements are practices or processes frequently shared by interventions or implementations. Traditional common elements methodologies use synthesis, distillation, and statistics to describe and evaluate the merit of common ingredients in effective interventions. Recent developments include identifying and testing common configurations of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Therefore, the need to improve real-world implementation may outweigh the theoretical need to identify individual strategy effectiveness. In situations where it would be useful to isolate the impact of single strategies, we suggest that the same methods for documenting and analyzing the critical components (or core functions) of complex interventions [ 67 70 ] may help to identify core components of multifaceted implementation strategies [ 71 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the need to improve real-world implementation may outweigh the theoretical need to identify individual strategy effectiveness. In situations where it would be useful to isolate the impact of single strategies, we suggest that the same methods for documenting and analyzing the critical components (or core functions) of complex interventions [ 67 70 ] may help to identify core components of multifaceted implementation strategies [ 71 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were many studies evaluating numerous outcomes, risking data dredging. Further, the significant heterogeneity in the ways in which implementation outcomes are operationalized and reported is a substantial barrier to conducting large-scale meta-analytic approaches to synthesizing evidence for implementation strategies [ 67 ]. The field could look to others in the social and health sciences for examples in how to test, validate, and promote a common set of outcome measures to aid in bringing consistency across studies and real-world practice (e.g., the NIH-funded Patient-Reported Outcomes Measurement Information System [PROMIS], https://www.healthmeasures.net/explore-measurement-systems/promis ).…”
Section: Implications For Implementation Science: Four Recommendationsmentioning
confidence: 99%
“…During Exploration and Preparation, we propose that prioritizing function fidelity is essential to carefully identifying the key hypothesized drivers of change that are feasible to be implemented in a local context. Although we were limited in our ability to review, evaluate, and select intervention components based on existing evidence in the literature, we would recommend that future adopters of this approach follow more rigorous guidelines for assessing candidate forms to establish evidence-informed inclusion criteria ( 19 , 58 ). Edmunds’ et al's (2022) Components & Rationales for Effectiveness (CORE) Fidelity Method for identifying key components of EBPs offers highly relevant guidance for augmenting our approach by providing systematic guidelines for gathering and synthesizing information to develop a CORE model that outlines the essential intervention components to fulfilling each function and the possible forms by which this might occur ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kirk and colleague's (2021) case study of applying the function-form framework to streamlining the process of hospice referrals was guided by a literature review that identified forms listed in candidate intervention protocols, followed by qualitative interviews that could inform the post hoc identification of underlying functions (19). This form fidelity approach parallels other advancing methods for disentangling the building blocks of interventions so that they can be reassembled for best fit with the implementation environment, such as the common elements approach (58).…”
Section: Advancing Function Fidelity Throughout Epismentioning
confidence: 99%